Do Regulations and Insurance Knowledge Affect Insurance Demand? Evidence from Bicycle Insurance in Japan - Yoshihiro Asai (Risks, 2025)
Several empirical studies have attempted to clarify whether differences in regulations affect people’s behavior. However, due to a lack of data, few have attempted to clarify whether these differences affect the purchase of insurance. Therefore, in this study, I conducted a survey of consumers in Japan and analyzed the characteristics of those who bought bicycle insurance. My findings are as follows: First, users tend to purchase bicycle insurance in prefectures where it is compulsory. Second, bicycle users with a high level of insurance knowledge tend to purchase insurance. Third, consumers who use bicycles more frequently tend to purchase insurance.